The Influence of Living Necessities, Impulsive Buying, Hedonic Conformity on Students' Interest in Using Online Loan Services is Mediated by Perceived Ease of Use - Maharani, Esa Zulfamaylia; Indriasari, Ika; Utami, Ratih Hesty (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: This research was conducted with the aim of determining the influence of subsistence needs, impulsive buying, and hedonic conformity on PGRI University Semarang students' interest in using online loan services through perceived ease of use. Design/Method/Approach: This research is descriptive research with a quantitative approach because it is suitable to determine the influence of life needs, impulsive buying, and hedonic conformity on students' interest in using online loan services which is mediated by perceived ease of use. This research will take primary data, so the data collection technique will be carried out by distributing questionnaires online via Google Form to students who are interested in using online loan services. Research Finding: The research results of the impulsive buying and hedonic conformity variables show that there is no significant influence on students' interest in using online loan services, however the independent variables which are supported by connecting variables such as impulsive buying through perceived convenience show the results that there is a significant influence on students' interest in using online loan services. Meanwhile, the results for the necessities of life variable show a significant influence on students' interest in using online loan services. Research limitation: Research time creates limitations for researchers to maximize this research, lack of time to distribute questionnaires more widely because researchers are also working so the focus is divided between research and work. It is recommended that future researchers focus on research so that the results are more relevant, expand the population, and also add variables to increase knowledge about finance, especially fintech peer to peer lending.